Analisis Pengaruh Pajak Daerah, Retribusi Daerah, Dana Perimbangan, dan SiLPA terhadap Belanja Modal - Sugianoor Sugianoor; Saipudin Saipudin (PPJP Universitas Lambung Mangkurat, 2023)
This research aimed to analyze the effect of local taxes, levies, balance funds, and SiLPA on capital expenditures. The population used in this study were districts/cities in South Kalimantan, this study used quantitative research methods, and this data analysis technique used panel data with multiple linear regression and secondary data for nine years (2011-2019). Capital expenditures have an important role in improving public services, such as increasing the value of assets and obtaining assets, and improving public facilities with regional expenditures, which are effective in increasing the regional economy, such as increasing the useful life or adding value to road and bridge, irrigation and network assets.In the results of this study, the results of the linear regression analysis conducted show that the variables of Local Taxes and levies on districts and cities in South Kalimantan are not significant to capital expenditure and have a positive value, which means that the variables of Regional Taxes and Regional Levies have a significant relationship direction of Capital Expenditures but has no effect on Capital Expenditures. Balanced Funds in districts and cities in South Kalimantan have a positive value and significant effect on capital expenditure. Silpa in districts and cities in South Kalimantan has a significant positive effect on capital expenditure, which means that the Balanced Fund and SiLPA variables have a unidirectional relationship, meaning that it decreases. -the increase in the Balancing Fund and SiLPA variables in districts and cities in South Kalimantan affects capital expenditure